The discourse of NKRI (The Unitary State Republic of Indonesia) and caliphate in the Indonesian context - Siti Kholifah (Faculty of Social and Political Science, Universitas Airlangga, 2020)
This study’s primary focus is to examine the discourse of the NKRI (Unitary State of the Republic of Indonesia) and that of the caliphate that has been developing on social media. It involves essential issues because Indonesia’s state and religion have had a dynamic relationship since the New Order era. The debatable issue related to the state and religion shows that religion is a crucial subject used to maintain the state. As a state, Indonesia emphasizes multicultural values; however, some people or organizations have an intolerance of Indonesia’s plurality promoted on social media. Using Foucault’s theory on discourse, power, and knowledge, this study was conducted by applying big data to Social Network Analysis (SNA) through the netlytic program. Big data is a new method developed to analyze the social phenomena that happen in the digital era. This study examines the assumption that the discourse of the NKRI is not a single discourse in the Indonesian context. It is in addition to the caliphate’s discourse, although the NKRI is still the dominant discourse. The debatable issue within the discourse of the NKRI and the caliphate is related to dynamic religious organizations that are not based on cultural values. They tend to be either puritan (seeking to purify the doctrine) or radical. This situation is also related to the political context where the caliphate’s discourse is developing related to Jakarta’s local election. There is also the issue of the religious defamation conducted by Basuki Tjahaja Purnama (Ahok). This situation explains the increase in Islamic political roles that are not affected by the sociological context. The roles are more impacted by political elites who are using religion as a political vehicle.